Kearifan Lokal Masyarakat Desa Buntoi Kabupaten Pulang Pisau Dalam Pemanfaatan Rotan: Local Wisdom of The Buntoi Village Community in Pulang Pisau Regency in The Utilization of Rattan - Ginting, Ira Ersikeromla Br; Tanduh, Yusintha; Silvianingsih, Yosefin Ari; Herianto, Herianto; Hastari, Belinda (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
The community of Buntoi Village in Pulang Pisau Regency, especially women, has utilized rattan as a source of livelihood to support family economies and local culture. However, the local wisdom values of rattan utilization are generally only known by the local community, not the wider community. This study describes the processing and local wisdom values of rattan processing in the form of products and motifs. The research respondents were members of the Social Forestry Business Group (KUPS) rattan craftsmen in Buntoi Village, using purposive sampling techniques. Based on the data collected, it shows that rattan weaving is traditional knowledge passed down from ancestors as part of their interaction with the surrounding environment. The weaving motifs are inspired by natural forms, patterns, the surrounding environment, and cultural heritage. The local wisdom values include cultural values found in 13 weaving motifs and 10 motifs of creativity, as well as values of precision and patience, which significantly influence the quality of rattan weaving